Cochlear implant electrode design for safe and effective treatment - Dhanasingh, Anandhan; Nielsen, Stefan Bryde; Beal, Fabrice; Schilp, Soeren; Hessler, Roland; Jolly, Claude; Hochmair, Ingeborg (Frontiers in Neurology, 2024)
The optimal placement of a cochlear implant (CI) electrode inside the scala tympani compartment to create an effective electrode–neural interface is the base for a successful CI treatment. The characteristics of an effective electrode design includes (a) electrode matching every possible variation in the inner ear size, shape, and anatomy, (b) electrically covering most of the neuronal elements, and (c) preserving intra-cochlear structures, even in non-hearing preservation surgeries. Flexible electrode arrays of various lengths are required to reach an angular insertion depth of 680° to which neuronal cell bodies are angularly distributed and to minimize the rate of electrode scalar deviation. The current scientific evidence indicates at the time of writing this article that straight lateral wall electrode outperforms perimodiolar electrode by preventing electrode tip fold-over and scalar deviation. Most of the available literature on electrode insertion depth and hearing outcomes supports the practice of physically placing an electrode to cover both basal turn and middle turn of the cochlea This is only achievable with longer straight lateral wall electrodes since single-sized and pre-shaped perimodiolar electrodes have limitations in reaching beyond the basal turn of the cochlea and in offering consistent modiolar hugging placement in every cochlea. For malformed inner ear anatomies that lack a central modiolar trunk, the perimodiolar electrode is not an effective electrode choice. Most of the literature has failed to demonstrate superiority in hearing outcomes when comparing perimodiolar electrodes with straight lateral wall electrodes from single CI manufacturers. In summary, flexible and straight lateral wall electrode type is reported to be gentle to intra-cochlear structures and has the potential to electrically stimulate most of the neuronal elements which are necessary in bringing full benefit of the CI device to recipients.